The Relationship Between Coach-Athlete Intimacy and Anxiety Ahead of the Match at Athletes in Tapak Suci Sidoarjo: Hubungan Antara Intimasi Pelatih – Atlet dengan Kecemasan Menjelang Pertandingan pada Atlet Tapak Suci Sidoarjo - Oktavianingrum, Rizky Sandra; Maryam, Effy Wardati (Universitas Muhammadiyah Sidoarjo, 2023)
The research was motivated by the phenomenon of athletes experiencing high anxiety before the match. This study aims to determine the relationship between coach-athlete intimacy and anxiety before the match in Tapak Suci Sidoarjo athletes. This research uses quantitative research with a correlational approach. The variables of this study were coach-athlete intimacy as the independent variable and anxiety before the match as the dependent variable. The study was conducted in Tapak Suci Sidoarjo with a total sample of 87 athletes from the entire population taken using a saturated sampling technique. The data collection technique used two Likert model psychological scales, namely the coach-athlete intimacy scale and the anxiety scale before the match. The hypothesis in this study is that there is a negative relationship between coach-athlete intimacy and anxiety before the match in Tapak Suci Sidoarjo athletes. Analysis of the data used is the analysis of the Pearson Product Moment Correlation technique using the SPSS 18 for windows program. The results of the data analysis of this study showed a correlation coefficient of -0.354 with a significance of 0.000. The effective contribution of coach-athlete intimacy with anxiety before the match for Tapak Suci Sidoarjo athletes is 12.5%. So there is a negative relationship between coach-athlete intimacy and anxiety before the match in Tapak Suci Sidoarjo athletes so that the hypothesis can be accepted.